REST corepressor 2 contributes to the cell proliferation of endometrial cancer - Zhu, Qingjuan; Yang, Xin; Lv, Yuchun (Frontiers in Oncology, 2025)
BackgroundUterine corpus endometrial cancer (UCEC) is a prevalent gynecological malignancy. REST corepressor 2 (RCOR2), a nuclear transcription co-repressor, has been implicated in various cellular processes. However, its regulatory role in UCEC progression remains unclear.MethodsRCOR2 expression levels were analyzed in UCEC tissues and cell lines using qPCR, Western blotting. Functional assays, including CCK8 and colony formation assays, were used to assess the impact of RCOR2 knockdown or overexpression on UCEC cell viability and proliferation.ResultsRCOR2 expression was significantly elevated in UCEC tissues compared to adjacent normal tissues. High RCOR2 expression correlated with advanced clinical stage, high histologic grade, and lymph node metastasis. ROC analysis indicated strong diagnostic value. RCOR2 expression showed a positive correlation with proliferation-related genes MKI67, CCND1, and PCNA. Functional assays revealed that RCOR2 knockdown suppressed, while overexpression promoted, proliferation of endometrial cancer cells. These effects were validated by CCK8 and colony formation assays, as well as changes in mRNA and protein levels of MKI67, CCND1, and PCNA, supporting RCOR2’s role in regulating UCEC cell proliferation.ConclusionsThese findings suggest that RCOR2 promotes endometrial cancer progression by enhancing tumor cell proliferation and may serve as a potential diagnostic and therapeutic target in UCEC.